Recent Advances in Total Synthesis via Metathesis Reactions - Cheng-Sánchez, Iván; Sarabia, Francisco (Synthesis, 2018)
The metathesis reactions, in their various versions, have become a powerful and extremely valuable tool for the formation of carbon–carbon bonds in organic synthesis. The plethora of available catalysts to perform these reactions, combined with the various transformations that can be accomplished, have positioned the metathesis processes as one of the most important reactions of this century. In this review, we highlight the most relevant synthetic contributions published between 2012 and early 2018 in the field of total synthesis, reflecting the state of the art of this chemistry and demonstrating the significant synthetic potential of these methodologies.1 Introduction2 Alkene Metathesis in Total Synthesis2.1 Total Synthesis Based on a Ring-Closing-Metathesis Reaction2.2 Total Synthesis Based on a Cross-Metathesis Reaction2.3 Strategies for Selective and Efficient Metathesis Reactions of Alkenes2.3.1 Temporary Tethered Ring-Closing Metathesis2.3.2 Relay Ring-Closing Metathesis2.3.3 Stereoselective Alkene Metathesis2.3.4 Alkene Metathesis in Tandem Reactions3 Enyne Metathesis in Total Synthesis3.1 Total Syntheses Based on a Ring-Closing Enyne-Metathesis Reaction3.2 Total Syntheses Based on an Enyne Cross-Metathesis Reaction3.3 Enyne Metathesis in Tandem Reactions4 Alkyne Metathesis in Total Synthesis4.1 Total Synthesis Based on a Ring-Closing Alkyne-Metathesis Reaction4.2 Other Types of Alkyne-Metathesis Reactions5 Conclusions
Keywords: alkene metathesis; alkyne metathesis; enyne metathesis; natural products; total synthesis